Hunting as a conservation tool : investigating the use of hunting in CBNRM programs : a case study of the Ntabethemba Community Reserve, South Africa. - Gird, Justin William (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.